Representasi Subaltern dalam Novel Anak Siapa? karya Thio Tjin Boen: Analisis Poskolonial melalui Kerangka Teoretis Gayatri Chakravorty Spivak - Yusri Arifah Aminnur (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
This study examines the representation of the subaltern and the forms of resistance articulated in the novel Anak Siapa? by Thio Tjin Boen through Gayatri Chakravorty Spivak’s theory of subalternity within a postcolonial literary framework. The research addresses how the characters embody subaltern positionality and how resistance is negotiated within colonial and patriarchal power structures. Employing a qualitative approach with a descriptive-analytical method, the study analyzes textual data drawn from narrative passages, dialogues, and character interactions that depict marginalization, subordination, and contestation. The findings reveal that subalternity is represented primarily through indigenous female characters deprived of bodily autonomy and decision-making authority, as well as through Peranakan Chinese figures occupying an ambiguous status within the colonial hierarchy. Resistance emerges in moral defiance, symbolic refusal, and moments of vocal assertion; however, these acts remain circumscribed by dominant colonial discourses. The study argues that the novel reflects the layered complexity of subaltern experience in early twentieth-century Peranakan Chinese literature and problematizes the possibility of fully articulating subaltern agency under colonial domination.